Post-translational and transcriptional dynamics – regulating extracellular vesicle biology. (2nd January 2019) - Claridge, Bethany; Kastaniegaard, Kenneth; Stensballe, Allan; Greening, David W.
ABSTRACT: Introduction : Extracellular vesicles (EVs) are secreted into their extracellular environment, contain a specific repertoire of cellular cargo, and represent a novel vehicle for cell–cell communication. Protein post-translational modifications (PTMs) are emerging as major effectors of EV biology and function, and in turn, regulate cellular signaling. Areas covered : Discovery and investigation of PTMs such as methylation, glycosylation, acetylation, phosphorylation, sumoylation, and many others has established fundamental roles for PTMs within EVs and associated EV function. The application of enrichment strategies for modifications, high-resolution quantitative mass spectrometry-based proteomics, and improved technological approaches have provided key insights into identification and characterization of EV-based PTMs. Recently, an overwhelming appreciation for the diversity of modifications, including post-transcriptional modifications, dynamic roles of these modifications, and their emerging interplay, including protein–protein, protein–lipid, protein–RNA, and variable RNA modifications, is emerging. At a cellular level, such interplay is essential for gene expression/genome organization, protein function and localization, RNA metabolism, cell division, and cell signaling. Expert commentary : The understanding of these modifications and interactions will provide strategies toward how distinct cargo is localized, sorted, and delivered through EVs to mediate intercellular function, with further understanding of such modifications and intermolecular interactions will provide advances in EV-based therapeutic strategies.